1994
DOI: 10.1002/jcp.1041600203
|View full text |Cite
|
Sign up to set email alerts
|

EGF modulates phosphoinositide levels in ovarian granulosa cells stimulated by luteinizing hormone

Abstract: Hamster granulosa cells were exposed to epidermal growth factor (EGF) and luteinizing hormone (LH) to study cross-talk between second messenger pathways involving tyrosine kinase, cAMP, and phosphoinositides. Granulosa cells from ovarian preovulatory follicles of PMSG-primed hamsters were incubated with various additives in serum-free medium. LH, but not EGF, stimulated inositol phosphate (IP) accumulation; however, when combined with LH, EGF inhibited IP accumulation in a manner that was concentration depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We considered the possibility that EGF dowregulates AngII surface receptor density through the production of cAMP, since cAMP has been shown to downregulate AngII receptors (Chen et al, 1994) and since EGF has been shown to promote the formation of cAMP (Ball et al, 1990; Budnik and Mukhopadhyay, 1991; Hubbard, 1994; Chen et al, 1995). To determine if cAMP downregulates AngII surface receptors in cultured VSMC, we incubated VSMC with stable cAMP analogues overnight and then determined AngII surface binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We considered the possibility that EGF dowregulates AngII surface receptor density through the production of cAMP, since cAMP has been shown to downregulate AngII receptors (Chen et al, 1994) and since EGF has been shown to promote the formation of cAMP (Ball et al, 1990; Budnik and Mukhopadhyay, 1991; Hubbard, 1994; Chen et al, 1995). To determine if cAMP downregulates AngII surface receptors in cultured VSMC, we incubated VSMC with stable cAMP analogues overnight and then determined AngII surface binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…That it supports yolk formation by suppressing cAMP levels in the follicle is suggested by two results: the effects of PTX on follicles, in particular the increases in Clexchange, K + uptake, and fluid uptake that result in the termination of epithelial patency, are also evoked by cell-permeant analogs of cAMP; and second, PTX-treatment resulted in a 34% increase in the cAMP content of follicles within 30 min. This degree of increase is also elicited by PTX in several mammalian cell lines (Bohm et al, 1994;Hubbard, 1994). The follicle is a multicompartmented system, however, and it is thus possible that the increase measured here is greater than 34% in the follicle cells, where PKA is mainly localized (Wang, 1996).…”
Section: Discussionmentioning
confidence: 70%
“…Evidence for negative regulation of phospholipase C by G-proteins exists in a thyroid cell line FRTL5 and in ovarian granulosa cells (Bizzarri et al, 1990;Hubbard, 1994). In FRTL5 cells carbachol, a muscarinergic agonist, inhibits basal and norepinephrine-induced inosi-to1 phosphate generation in a pertussis toxin-sensitive fashion.…”
Section: Discussionmentioning
confidence: 99%